Fundamental and estimation of thermal contact resistance between polymer matrix composites: A review. (15th June 2022) - Zhou, Tian; Zhao, Yejing; Rao, Zhenghua
Highlights: Experimental measurement and prediction methods to estimate PMCs' TCR are reviewed. Factors affecting thermal conductance on rough surface of PMC are discussed. Main challenges for accurately estimating TCR between PMCs are summarized. Potential estimation methods such as multi-scale simulation and machine learning are proposed. Abstract: The thermal contact resistance (TCR) between polymer matrix composites (PMCs) imposes the significant impacts on the design, processing and application of these materials. This paper reviews the fundamental of the interfacial thermal conductance mechanism by analyzing the effects of inherent material properties, surface topography and working conditions of PMCs on TCR. Experimental measurement and numerical modeling methods are addressed to identify the distinct characteristics for estimating the TCR between PMCs. The main challenges for the accurate estimation are summarized, mainly including the complex interfacial thermal conductance due to the addition of fillers, the anisotropic thermal and mechanical responses due to the heterogeneity of PMCs, the uncertain contact mechanics due to the special mechanical properties. Finally, the multiscale estimation and machine learning methods are proposed for the further study on TCR between PMCs. This review is important because it provides guidance for the future studies in the interfacial thermal conductance between PMCs and thus the wide applications of emerging composites.